2020
DOI: 10.30737/ukarst.v4i2.1020
|View full text |Cite
|
Sign up to set email alerts
|

Direct Shear Strength of Clay Reinforced with Coir Fiber

Abstract: Indonesia is the largest coconut producing country in the world. However, the resulting coir waste is still rarely used for structural materials. This research studied the effect of random inclusion of coir fiber on the shear strength of clay with high plasticity. The carried test in this study is a direct shear strength test. The fiber content variations used are 0%, 0.25%, 0.50%, 0.75%, and 1% of the dry weight of the mixture with a fiber length of between 30 mm to 50 mm. The results show that the reinforcem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…They presented improvements in mechanical properties such as UCS values, shear-strength parameters, and flexibility. Previous research found that coir fibre improves the stiffness, strength [48], and bearing capacity of clay soil [49].…”
Section: Unconfined Compression-strength Testmentioning
confidence: 99%
“…They presented improvements in mechanical properties such as UCS values, shear-strength parameters, and flexibility. Previous research found that coir fibre improves the stiffness, strength [48], and bearing capacity of clay soil [49].…”
Section: Unconfined Compression-strength Testmentioning
confidence: 99%
“…Se conformaron tres muestras de suelo fino de consistencia blanda, y fibra de cáñamo de 4 cm de longitud, con dos diferentes proporciones de cáñamo según el peso seco requerido para cada ensayo, asignando las muestras como Arcilla Patrón, A p , Arcilla con 0.5 % de cáñamo, A0.5 %, y Arcilla con 0.75 % de Cáñamo, A 0.75 % (Abou Diab et al, 2018;Mazhoud et al, 2017;Widianti y Diana, 2020). El material que se seleccionó para reunir las tres mezclas de suelo, se obtuvo del resultado de la excavación realizada en la operación de pilotaje del edificio de posgrados de la Universidad Pedagógica y Tecnológica de Colombia [UPTC] ubicado en la zona urbana nororiental de la ciudad de Tunja.…”
Section: Materialesunclassified
“…1). Widianti et al [25] have tested the soil's engineering properties in previous studies, as shown in Table 1. Table 1 shows that the clay which was used is high plasticity clay.…”
Section: Soilmentioning
confidence: 99%
“…Several studies conducted UCS tests from soil mixed with coir fiber and other materials, including lime [16], using a mixture of bentonite, lime, gypsum [17], rice husk ash [6], [18], [19], fly ash [20], lime and coir fiber ash [16], carbon tetrachloride & sodium hydroxide [21], polypropylene fiber [22], basalt fiber [23], organic polymers and sisal fiber [24]. Widianti et al [25] have studied direct shear strength on clay strengthened with coconut fiber. The maximum shear strength is generated at fiber content of 0.75%.…”
Section: Introductionmentioning
confidence: 99%